Final answer:
To find the equation of the circle with center (-3, 4) and passing through (4, -2), we determine the radius using the distance formula and plug it into the standard form of a circle's equation, resulting in (x + 3)^2 + (y - 4)^2 = 85.
Step-by-step explanation:
To find the equation of a circle, we can use the standard form (x - h)^2 + (y - k)^2 = r^2, where (h, k) is the center of the circle and r is the radius. Given the center at (-3, 4) and a point on the circle (4, -2), we first calculate the radius by finding the distance between these two points using the distance formula:
d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2}
r = \sqrt{(4 - (-3))^2 + (-2 - 4)^2} = \sqrt{7^2 + (-6)^2} = \sqrt{49 + 36} = \sqrt{85}
So the equation of the circle is:
(x + 3)^2 + (y - 4)^2 = (\sqrt{85})^2
(x + 3)^2 + (y - 4)^2 = 85
This is the equation of the circle with center (-3, 4) that passes through the point (4, -2).